PERAN SPIRITUAL LEADERSHIP TERHADAP EMPLOYEE PERFORMANCE MELALUI EMPLOYEE WELL BEING PADA PEGAWAI DINAS PENDIDIKAN - Purwanto, Edi; Asyhari, Asyhari (Jurnal Manajemen Pendidikan, 2025)
This study aims to examine the impact of spiritual leadership on employee performance through employee well-being among employees of the Semarang City Education Office. Spiritual leadership, which emphasizes vision, altruistic love, and hope/faith, is considered an important factor in enhancing employees’ psychological well-being and organizational outcomes. The research employed a quantitative approach using a survey method. A Likert scale questionnaire (1–5) was distributed to the entire population of 110 employees. Data were analyzed using Partial Least Squares (PLS) with SmartPLS 3.0, including validity and reliability testing, as well as outer model, inner model, and hypothesis testing. The findings reveal that spiritual leadership has a significant positive effect on employee well-being, employee well-being significantly improves employee performance, and spiritual leadership also directly affects employee performance. Furthermore, employee well-being mediates the relationship between spiritual leadership and employee performance. The results confirm the essential role of spiritual leadership in fostering employee well-being, which subsequently enhances employee performance. The practical implication highlights the importance of strengthening spiritual leadership practices and improving employee well-being programs within government institutions.